A genome-wide association study integrated with single-cell and bulk profiles uncovers susceptibility genes for nasopharyngeal carcinoma involved in tumorigenesis via regulation of T cells - Tong-Min Wang; Wen-Li Zhang; Jin-Ru Xie; Yong-Qiao He; Minzhong Tang; Wen-Qiong Xue; Da-Wei Yang; Chang-Mi Deng; Hua Diao; Zhi-Ming Mai; Ruo-Wen Xiao; Ying Liao; et al. (Genome Biology)
Abstract Background Nasopharyngeal carcinoma is an aggressive malignancy originating from the nasopharyngeal mucosa and associated with genetic factors. Many nasopharyngeal carcinoma susceptibility loci have been identified by genome-wide association studies (GWASs), but their underlying functional insights are largely unexplained. Results A meta-GWAS including 5073 nasopharyngeal carcinoma patients and 5860 controls from nasopharyngeal carcinoma endemic areas identifies a total of 863 significant SNPs, including SNPs at a novel locus 3p24.1 (rs56365817; nearby genes: CMC1/EOMES). By integrating the GWAS signals with single-cell and bulk profiles, we find nasopharyngeal carcinoma susceptibility robustly associated with T cells in different methods and datasets. In nasopharyngeal carcinoma-associated cell type, we identify 234 putative susceptibility genes (81.62% of them novel), mainly enriched in immune-related biological processes. Five putative causal genes are prioritized. We perform in-depth bioinformatic analysis and functional experiments for EOMES, finding that the nasopharyngeal carcinoma-risk alleles of four functional SNPs upregulate EOMES expression by promoting the activity of regulatory elements in T cells, and EOMES participates in nasopharyngeal carcinoma tumorigenesis via regulation of CD8+ T cell exhaustion in the tumor microenvironment. Conclusions This study uncovers novel nasopharyngeal carcinoma susceptibility genes and their functional cell types, which improves the understanding of nasopharyngeal carcinoma genetic etiology.